PERBEDAAN KECEMASAN KORBAN PELECEHAN SEKSUAL SECARA OFFLINE DANONLINE PADA DEWASA AWAL - Anisah Zahra; Widyastuti, Nurfitriany Fakhri (Jurnal Kesehatan, 2025)
Sexual harassment anxiety is a concern about situations that threaten individuals with all kinds of unwanted sexual behavior. Anxiety is the most common symptom felt when experiencing sexual harassment, so steps need to be taken to minimize it. This study aims to determine the differences in anxiety of victims of sexual harassment offline and online in early adulthood. This study used an accidental sampling technique and was conducted on 205 respondents, early adults aged 18-40 years who had experienced sexual harassment either offline or online in Makassar. This study used the sexual harassment and anxiety scale DASS 42, the results of which were analyzed by Kruskal Wallis and Mann-Whitney using the JASP 0.16.0. The significance value obtained is 0.014 (p<0.05), which means that there are differences in anxiety about offline and online sexual harassment in early adulthood. This research has implications for social and clinical psychology, especially with regard to anxiety sexual harassment